2010
DOI: 10.1074/jbc.m109.091058
|View full text |Cite
|
Sign up to set email alerts
|

t-SNARE Protein Conformations Patterned by the Lipid Microenvironment

Abstract: The spatial distribution of the target (t-)SNARE proteins (syntaxin and SNAP-25) on the plasma membrane has been extensively characterized. However, the protein conformations and interactions of the two t-SNAREs in situ remain poorly defined. By using super-resolution optical techniques and fluorescence lifetime imaging microscopy, we observed that within the t-SNARE clusters syntaxin and SNAP-25 molecules interact, forming two distinct conformations of the t-SNARE binary intermediate. These are spatially segr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 44 publications
7
82
1
Order By: Relevance
“…Syntaxin1A clusters had variable sizes, with a median FWHM of ϳ68 nm (Fig. 1i), which is comparable with the size estimated in previous studies in PC-12 cells using STED (5), dSTORM (41,67), and PALM (68). The molecular density in syntaxin1A clusters in the PM of INS-1 cells was 20.5 Ϯ 6.7 per cluster (n ϭ 95 from 7 cells), equivalent to 41.0 Ϯ 13.4 per cluster after considering 50% photoactivation efficiency for PAmCherry1 (66).…”
Section: Resultssupporting
confidence: 73%
“…Syntaxin1A clusters had variable sizes, with a median FWHM of ϳ68 nm (Fig. 1i), which is comparable with the size estimated in previous studies in PC-12 cells using STED (5), dSTORM (41,67), and PALM (68). The molecular density in syntaxin1A clusters in the PM of INS-1 cells was 20.5 Ϯ 6.7 per cluster (n ϭ 95 from 7 cells), equivalent to 41.0 Ϯ 13.4 per cluster after considering 50% photoactivation efficiency for PAmCherry1 (66).…”
Section: Resultssupporting
confidence: 73%
“…6c), which showed clustered syntaxin-EGFP with an average width (FHWM) of 103±4 nm (n ¼ 74). This is slightly larger than previous estimates of syntaxin cluster size (60-90 nm; refs 28,43,45,46), possibly due to the use of live rather than fixed cells or higher precision of the earlier measurements. Visually, two types of syntaxin behaviour were apparent: one of apparently random diffusion and another where molecules were temporarily confined to a small area, often beneath a granule (Fig.…”
Section: Visit)contrasting
confidence: 46%
“…We observed striking differences in the amount of SNAP25 or munc13 between clusters, likely as a consequence of slow recruitment. This may in part explain why the interaction between syntaxin and SNAP25 (measured as FRET) varies from cluster to cluster 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mutating the domain 3a loop of Munc18-1 on these other interactions warrants further investigation. Furthermore, Sx1a is known to form 40-70 nm nanoclusters at the cell surface (Bar-On et al, 2012;Rickman et al, 2010), which correlate with sites of SG exocytosis (Barg et al, 2010). While our study has shown that Sx1a is delivered to the cell surface by Munc18-1 D317-333 , possible effects on the distribution of Sx1a into microdomains, and the underlying nanoarchitecture of these domains, remains unknown.…”
Section: Discussionmentioning
confidence: 73%